Obedience Pressure vs. Peer Pressure: An Explanation of Muslims’ Religious Role in Budgetary Slack - Aryan Danil Mirza. BR; Kharisa Rachmi Khoirunisa (Faculty of Economics and Business, Universitas Gadjah Mada, 2021)
Introduction/Main Objectives: The performance of individuals in organizations is generally evaluated based on their success at achieving targets. Furthermore, the role of the budget has a major effect on individual behavior in the preparation of the budget, by allowing unethical actions (budgetary slack). Background Problems: There are a few studies that measure the difference in the influence of social pressure between superiors and peers on individual’s behavior in the organizational budgeting process. On the other hand, there are inconsistencies in the results of the research into the role of religiosity in the creation of budgetary slack. Novelty: To explain why people are not influenced by social pressures to create budgetary slack, we use the Psychological Reactance Theory. We argue that religiosity is one factor that influences people in making decisions about participative budgeting. Religiosity is believed to be able to influence one's personal values, so it impacts on one's judgment and determination of whether a thing is good or bad. Research Methods: This study uses an experimental research method on 65 undergraduate accounting students and a 2x2 factorial design consisting of two factors, social pressure (obedience pressure and peer pressure) and religiosity (high and low). Finding/Results: The results show that religiosity is proven to play an important role in the budget decision-making process, futhermore it minimizes the occurrence of budgetary slack. Conclusion: Individuals who have high religiosity are proven to be better able to avoid creating budgetary slack compared to individuals who have low religiosity, when receiving pressure from superiors and peers. This result has implications for organizational stakeholders dealing with employee recruitment or in the organization's management control system, as religiosity is an important factor that must be prioritized.